Effect of heat treatment on the high temperature fatigue life of single crystalline nickel base superalloy additively manufactured by means of selective electron beam melting. (15th July 2019) - Meid, Carla; Dennstedt, Anne; Ramsperger, Markus; Pistor, Julian; Ruttert, Benjamin; Lopez-Galilea, Inmaculada; Theisen, Werner; Körner, Carolin; Bartsch, Marion
Abstract: The high temperature low cycle fatigue behavior of specimens manufactured from a single crystalline nickel base superalloy processed by selective electron beam melting (SEBM) has been investigated with respect to the effect of different heat treatments. The fatigue lifetime of heat treated material was significantly higher than that of as-built material. Applying hot isostatic pressing (HIP) with an integrated heat treatment resulted in even longer fatigue life. Lifetime limiting crack initiation occurred at interfaces of melting layers, at micro-porosity generated during solidification or, in HIP treated samples, at precipitates which formed at the location of collapsed pores. Graphical abstract: Unlabelled Image